2019
DOI: 10.1021/acsami.9b06608
|View full text |Cite
|
Sign up to set email alerts
|

Photoplastic Transformation Based on Dynamic Covalent Chemistry

Abstract: The magical fantasy of decades-old transformer characters is becoming closer to scientific reality, as transformable materials can change their shapes in response to thermal, mechanical, electrical, and chemical stimuli. However, precise and prompt control of plastic shaping remains to be wanted. Photoresponsive materials provide a promising alternative for rapid optomechanical shaping with limited success. Here, we report a new class of photoplastic transformation based on dynamic covalently crosslinked polyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
2
17
0
Order By: Relevance
“…The conversion from HABI to TPI can also be triggered by heat, light, or force, and the response to light has been used for self-healing. [79,80] The generated TPIs upon C-N bond cleavage endow the polymeric materials with a blue color.…”
Section: Radical-based Mechanochromophoresmentioning
confidence: 99%
“…The conversion from HABI to TPI can also be triggered by heat, light, or force, and the response to light has been used for self-healing. [79,80] The generated TPIs upon C-N bond cleavage endow the polymeric materials with a blue color.…”
Section: Radical-based Mechanochromophoresmentioning
confidence: 99%
“…Zhu et al 102 paid more interest to the photomechanical performance of HABI‐based photosensitive polymers. They demonstrated that HABI‐based polymers with photoplastic properties could be used in photo‐processing, self‐healing, photoplastic springs and photomechanical hydrogels.…”
Section: Photomechanical Mechanisms and Applicationsmentioning
confidence: 99%
“…They have designed and prepared 2‐Br‐tetrapropargyl‐HABI, which is copolymerized with dipropargyl polyethylene glycol ether and 1, 6‐diazide hexane by aid of click chemistry to obtain the cross‐linked polymer of PTA‐HABI gel (Figure 8). 102 A range of photo‐transformation and photo‐processing applications based on PTA‐HABI gels were conducted, including light‐induced swelling, light‐induced melting, light‐induced self‐healing, light cutting, light drilling, light reshaping, and micro‐etching 102 . To be important, light remodeling and light‐induced self‐healing are of great significance for the recycling of materials.…”
Section: Photomechanical Mechanisms and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations